Self-screened high performance multi-layer MoS2 transistor formed by using a bottom graphene electrode. Issue 45 (4th November 2015) - Qu, Deshun; Liu, Xiaochi; Ahmed, Faisal; Lee, Daeyeong; Yoo, Won Jong
Abstract : Investigating the carrier transport mechanism in a multi-layer MoS2 and high performance MoS2 FET enabled by a bottom graphene contact. Abstract : We investigated the carrier transport in multi-layer MoS2 with consideration of the contact resistance ( R c ) and interlayer resistance ( R int ). A bottom graphene contact was suggested to overcome the degradation of I d modulation in a back gated multi-layer MoS2 field effect transistor (FET) due to the accumulated R int and increased R c with increasing thickness. As a result, non-degraded drain current ( I d ) modulation with increasing flake thickness was achieved due to the non-cumulative R int . Benefiting from the low R c induced by the negligible Schottky barrier at the graphene/MoS2 interface, the intrinsic carrier transport properties immune to R c were investigated in the multi-layer MoS2 FET. ∼2 times the enhanced carrier mobility was attained from the self-screened channel in the bottom graphene contacted device, compared to those with top metal contacts.